Attracting Digital Natives as Talents: Assessing the Strength of Good Employer, Product Quality, and Information Credibility Perceptions on Intent to Apply - Wijaya, Nikodemus Hans Setiadi; Silalahi, Andrean Agaventa Silgirana; Lee, Luis Diego Dans (Philippine Management Review; Vol 30 (2023), 2023)
The evaluation of organizational talent attraction strategies has occupied a substantial collection of human resource management (HRM) research, motivated by wide-ranging shifts in employer branding and other attraction efforts. Across economies, these trends affect the younger talent pool who have more employment options and employer information at their disposal as digital natives in a globalized workforce. This study substantially builds on current literature by examining three conceptual triggers that can guide potential applicants’ understanding of employers – namely (1) Good Employer, or the perception of leadership quality and workplace policies that promote employee wellbeing in the organization, (2) Product Quality, or the perception of competitive advantages of the employer’s core product or service portfolio, and (3) Information Credibility, or the perception of truthful and complete information reporting by the employer – on Intent to Apply. While these triggers have been the subject of existing body of HRM research, this study explores a conceptual model that correlates the triggers individually with Intent to Apply and also in conjunction with Information Credibility as a mediating variable. The study applies the said conceptual framework among digital native (i.e., millennials and Generation Z) jobseekers in Indonesia. The results indicate that both Good Employer and Information Credibility perceptions have positive associations with Intent to Apply, while Product Quality perceptions do not. Both Good Employer and Product Quality perceptions have a positive association with Information Credibility as a mediating variable towards Intent to Apply. This study should then guide organizations to shift their employer brand improvements to strengthening comprehensive employee wellbeing programs and perceptions, as well as truthful public reporting of the implementation of these programs, in order to attract jobseekers.